1999
DOI: 10.1046/j.1365-2559.1999.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of p27Kip1 expression is correlated with increased cell proliferation but not expression of p21waf1 and p53, and human papillomavirus infection in benign and malignant tumours of sinonasal regions

Abstract: Loss of p27 expression correlates with increased cell proliferation in sinonasal tumours. Moreover, the expression appears to be associated with keratinization in SCCs of the paranasal sinus. These findings indicate that p27 expression may be a useful marker for the dysregulation of cell kinetics in these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Keleş et al [18] found that p21 expression was not associated with dysplasia and the degree of dysplasia in IP in their study. There was no significant correlation with tumor differentiation in spite of increased p21 expression in paranasal sinus SCCs that Saegusa et al [35] observed. Similarly, we found no significant difference in the level of p21 expression between IPs and paranasal SCCs.…”
Section: Discussionmentioning
confidence: 71%
“…Keleş et al [18] found that p21 expression was not associated with dysplasia and the degree of dysplasia in IP in their study. There was no significant correlation with tumor differentiation in spite of increased p21 expression in paranasal sinus SCCs that Saegusa et al [35] observed. Similarly, we found no significant difference in the level of p21 expression between IPs and paranasal SCCs.…”
Section: Discussionmentioning
confidence: 71%
“…The loss of p27 expression has been correlated with a high degree of malignancy in many human cancers. Saegusa et al [32] demonstrated that the average p27 scores were inferior to normal levels in malignant lesions. In contrast to this study, Oncel et al [31] did not find significant differences between p27 expression in SNIPs and sinonasal SCC.…”
Section: Hpvmentioning
confidence: 99%
“…Saegusa et al identified weak to strong p27 immunoreactivity in inverted and exophytic papillomas. The author demonstrates that the loss of the p27 expression correlates with the increase of cell proliferation in sinonasal tumors (51) of action of HPV in oncogenesis have been attributed to its ability to render the p53 tumor suppressor gene of the host cell ineffective. The mutation of the p53 gene is currently the most commonly identified gene mutation in human neoplasia (52).…”
Section: Cytogenetics and Molecular Geneticsmentioning
confidence: 99%